Tax Contracts and Elections - Hans Gersbach; Maik T. Schneider (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
In this paper we examine the impact of tax contracts as a novel institution on elections, policies, and welfare. We consider a political game in which three parties compete to form the government. Parties have policy preferences about the level of public-good provision and benefit from perks when in office. A government raises taxes for both purposes. We show that tax contracts yield moderate policies and lead to lower perks by avoiding the formation of grand coalitions in order to win government. Moreover, in polarized societies they unambigously improve the welfare of the median voter.
Keywords: D72; D82; H55; 330; political contracts; elections; government formation; tax promise; Steuerpolitik; Asymmetrische Information; Regierungskoalition; Medianwähler-Modell; Neue politische Ökonomie; Theorie